Utilization of Oil Palm Wastes and Recycled Plastic as Raw Materials for Wood-Plastic Composites - Lusita Wardani; Muhammad Y Massijaya; Muhammad F Machdie (Jurnal Ilmu dan Teknologi Kayu Tropis, 2012)
This study examined the physical and mechanical properties of wood plastic composites made from recycled propypropylene (RPP) and oil palm biomass wastes under various particle sizes and pressing temperatures. Oil-palm biomass wastes (ie., oil palm trunk(OPT) was used as filler. The OPT was produced in 3groups (i.e., passed from 20, 40,and 60 meshes filtered). The RPP and OPT or EFB ratio were 7:3. Maleic anhydride (MAH) and benzoil peroxyde (BPO) were used as a modifier and an inisiator in amount of 5% based on RPP and MAH weight, respectively. The hand-mixtures of RPP and OPT or EFB with or without MAH and BPO were subjected to hot-press at 180 ⁰C and 190 ⁰C for 10 min at 15 kgf cm-2 pressure. The results indicated particle sizes, MAH and BPO and pressure of temperature were influences of physical and mechanical properties of WPC from OPT. Samples WPC with MAH and BPO have a highest value than samples without MAH and BPO. Testing was done according to standard JIS A 5908-2003. Preliminary research results shown that particle from palm oil trunk with additive content shown the best physical and mechanical properties compared to the others.Key words: benzoil peroxide, empty fruit bunches, maleic anhydride, oil palm trunk, particle size, recycle polypropylene